Чи могли бути точки зіткнення положень класичної генетики та «мічуринської біології»? - Стельмах, А.Ф. (Фактори експериментальної еволюції організмів, 2014)
Aims. To compare some theses of modern plant genetics and the views of “lysenkoists”. Methods. Utilization of scientific literature data and personal experience. Results. Supporters of “lysenkoism” denied the chromosomal theory of heredity and maintained the straight “inheritance of acquired traits”. Modern plant genetics assert that from coded in the individual genome genetic information to its implementation into the trait there are realizing the complex of innerorganism and genotype-environment interactions, during which the trait “genetic formula” is reconstructing. Genotype of realized character may be identified (and inherited) for certain environment only, under other conditions (with different stress factors) genotype of complex traits is found to be changed (and these changes are inherited, however in such environment only!). Does this thesis differ from the “inheritance of acquired traits”?! Conclusions. Irreconcilable contradictions of classical geneticists and supporters of “Michurin’s biology (=lysenkoists)” views are almost entirely removed with modern “Theory of the ecology-genetic organization of quantitative traits”.

Key words: “lysenkoism”, modern plant genetics, quantitative traits, likeness of views.